Hubungan Kinerja Manajerial terhadap Pengalaman Kerja dan Gaya Kepemimpinan - Mahaputra, M. Ridho (Siber Nusantara Publisher, 2023)
Abstract: The Literature Review article on the Relationship between Managerial Performance and Work Experience and Leadership Style is a scientific article that aims to build a research hypothesis on the influence of variables to be used in further research, within the scope of Human Resource Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are that: 1) Managerial Performance is related to Work Experience; 2) Managerial Performance relates to Work Experience; and 3) Work Experience related to Leadership Style. Apart from these exogenous variables that influence endogenous variables, there are many other factors including the variables of Education, Work Motivation and Work Environment. Abstrak: Artikel Literature Review Hubungan Kinerja Manajerial terhadap Pengalaman Kerja dan Gaya Kepemimpinan merupakan artikel ilmiah yang bertujuan membangun hipotesis riset pengaruh antar variabel yang akan digunakan pada riset selanjutnya, dalam ruang lingkup ilmu Manajemen Sumber Daya Manusia. Metode penulisan artikel Literature Review ini adalah dengan metode library risearch, yang bersumber dari media online seperti Google Scholar, Mendeley dan media online akademik lainnya. Hasil artikel Literature Review ini adalah bahwa: 1) Kinerja Manajerial berhubungan terhadap Pengalaman Kerja; 2) Kinerja Manajerial berhubungan terhadap Pengalaman Kerja; dan 3) Pengalaman Kerja berhubungan terhadap Gaya Kepemimpinan. Selain dari variabel exogen ini yang mempengaruhi variabel endogen, masih banyak faktor lain di antaranya adalah variabel Pendidikan, Motivasi Kerja dan Lingkungan Kerja.